Airflow study of air-cooled chillers installed at different floor level / Nur Faranini Zamri - Zamri, Nur Faranini (2020)
The arrangement of air-cooled chillers is one of the important factors to efficiently reject heat to the atmosphere. In this work, two units of air-cooled chillers are installed on different floor level. This arrangement affects the ACC units and leads to system failure. CFD simulation is conducted to observe the airflow of the actual arrangement. Two conditions are simulated in this study which are no-wind and with-wind condition. Sensitivity analysis is conducted to obtain the appropriate computational domain for the simulation. The effects of varying the distance between the ACCs is also analysed with six different spacing (3.6 m, 4.0 m, 5.0 m, 6.0 m, 7.0 m and 8.0 m). The effects of installing a barrier between the units is observed with five proposed barrier height (2.04 m, 2.34 m, 2.64 m, 2.94 m and 3.24 m). The airflow for each case is analysed in terms of velocity and temperature distribution, the velocity streamline and the velocity vector. For the actual arrangement of the ACCs, the hot air discharged accumulated at the top and between the units, due to inadequate space for circulation of air. Varying the distance between the ACCs does not improve the circulation of hot air between the units. Increasing the spacing between the units only add up the area needed for installation. The barrier installed separates the hot air discharged from flowing to the unit besides it. Due to the limited space for circulation of air, the hot air accumulates in between the units and the barrier. Each height of barrier gives different circulation of air at the area of interest. From the results, the recommended barrier height to overcome the problems occurred is 2.94 m.